Gone to the Spirits: A Transgender Prophet on the Columbia Plateau - O’Brien, Suzanne Crawford (Theology & sexuality, 2015)
This article examines the life of Kaúxuma núpika, an indigenous transgender prophet living on the Columbia Plateau in the early nineteenth century. As a Ktunaxa woman, she crossed cultural boundaries to marry a Euroamerican. When she left her husband, insisting on her independence and autonomy, she crossed another frontier. When Kaúxuma núpika declared herself no longer a woman, but a man, and secured himself a wife, he crossed further boundaries of gender and sexuality. As a warrior and a prophet, Kaúxuma núpika crossed the boundaries to the world of the spirit, returning with warnings, guidance, and hope for the tribal people of the Columbia River valley. In this project, I reflect upon the historical record in light of indigenous prophet traditions on the Columbia Plateau and current scholarship on gender and power among Native communities of the region, to consider notions of power, identity, and the religio-cultural dynamics of gender and sexual identity among indigenous communities on the Columbia Plateau.